2004
DOI: 10.1021/la030257l
|View full text |Cite
|
Sign up to set email alerts
|

Surface Stress, Kinetics, and Structure of Alkanethiol Self-Assembled Monolayers

Abstract: The surface stress induced during the formation of alkanethiol self-assembled monolayers (SAMs) on gold from the vapor phase was measured using a micromechanical cantilever-based chemical sensor. Simultaneous in situ thickness measurements were carried out using ellipsometry. Ex situ scanning tunneling microscopy was performed in air to ascertain the final monolayer structure. The evolution of the surface stress induced during coverage-dependent structural phase transitions reveals features not apparent in ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
160
4
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(180 citation statements)
references
References 79 publications
10
160
4
4
Order By: Relevance
“…52,53) In experiments on 200-nm-sized-grained films it was also found that the stress takes several hours to build. 54,55) Such cantilevers have important medical applications as sensors. 56) The fact that such large stress differences were detected in the CXD experiment indicates that the structure of the SAM must be very different between the flat and the curved surface regions of the nanocrystal.…”
Section: In-situ Thiolation Of Au Nanocrystalmentioning
confidence: 99%
“…52,53) In experiments on 200-nm-sized-grained films it was also found that the stress takes several hours to build. 54,55) Such cantilevers have important medical applications as sensors. 56) The fact that such large stress differences were detected in the CXD experiment indicates that the structure of the SAM must be very different between the flat and the curved surface regions of the nanocrystal.…”
Section: In-situ Thiolation Of Au Nanocrystalmentioning
confidence: 99%
“…Furthermore, it indicates surface stress change observed during the first introduction is unambiguously associated with SAM formation on sensing cantilever. Previous reports [4] have indicated that distance of cantilever to the location where alk:anethiol droplets are introduced, condition of gold surface like cleanliness and roughness, and grain structure of the gold on the cantilever's surface affects the kinetics and magnitude of surface stress development. Among those conditions, the microstructure of gold film significantly influences the development of the surface stress during the formation of Alkanethiol SAMs [4].…”
Section: Resultsmentioning
confidence: 99%
“…al. [3], SAMs have been used as test system for almost all cantilever based sensing techniques [4][5][6]. This is because they are relatively easy to prepare, form well-ordered close packed films and offers limitless possibilities of variations in chain length, end group and ligand attachments [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,38 In addition, the form of the present solution suggests that it may be applicable to more general coated-cantilever systems whose behaviors are governed by two competing time constants ͑not necessarily related to coating eigenstrain or viscoelasticity͒. 39 Examples of other mechanisms that could be accounted for by the current solution ͑or its extension͒ include growth kinetics/ molecular rearrangement in self-aligned monomers on goldcoated cantilevers 40,41 and cantilever actuation using polyelectrolyte brushes. 42 These applications involve relaxation phenomena that appear to contribute to observed overshoot responses in certain instances, although this behavior has yet to be placed upon a firm theoretical foundation.…”
Section: Summary Conclusion and Future Workmentioning
confidence: 98%